2012
DOI: 10.1086/664039
|View full text |Cite
|
Sign up to set email alerts
|

Conspicuous Consumption versus Charitable Behavior in Response to Social Exclusion: A Differential Needs Explanation

Abstract: Social exclusion has been shown to produce a number of different responses. This research examines the proposition that social exclusion may produce either selffocused or prosocial responses, depending on which needs are threatened. Different types of social exclusion threaten different needs, which in turn produce distinct outcomes (differential needs hypothesis). Social exclusion in the form of being implicitly ignored increased conspicuous consumption, whereas being explicitly rejected increased helping and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
361
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 334 publications
(375 citation statements)
references
References 33 publications
(63 reference statements)
9
361
2
3
Order By: Relevance
“…For example, Lee and Shrum (2012) demonstrated that being ignored poses a threat to one"s need for control and meaningful existence, which increases conspicuous consumption. Likewise, Mead, Baumeister, Stilton, Rawn and Vohs (2011) demonstrated that experiencing social exclusion motivates individuals to spend more on consumer products that could restore their social connectedness, providing a way to overcome the threat to their need for belonging.…”
Section: Ostracism Psychological Needs and Consumer Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Lee and Shrum (2012) demonstrated that being ignored poses a threat to one"s need for control and meaningful existence, which increases conspicuous consumption. Likewise, Mead, Baumeister, Stilton, Rawn and Vohs (2011) demonstrated that experiencing social exclusion motivates individuals to spend more on consumer products that could restore their social connectedness, providing a way to overcome the threat to their need for belonging.…”
Section: Ostracism Psychological Needs and Consumer Behaviourmentioning
confidence: 99%
“…On the other hand, feelings of ownership can develop even if a person does not actually own an object (see Reb & Connolly, 2007), and so feeling excluded could make nonowners value the opportunity to acquire consumer goods (Lee & Shrum, 2012), resulting in a higher WTP. Studies 2, 3, and 4 further tested whether ostracism influences how people value their possessions, by asking people about items that they already owned (which, arguably, are more appropriate for testing the model of ownership).…”
Section: Overview Of Studies 1 Tomentioning
confidence: 99%
“…Furthermore, this research advanced the motivation of lonely consumers from social-reconnection to self-safety concern. Previous literature mainly concentrated on the social reaction behaviors of lonely consumers, indicating that they are more likely to choose minority products to be unique and get social attention [54], and conduct prosocial behaviors such as donating more money to charity [55] and being more willing to help others [56]. Unlike these social behaviors, our research suggested that lonely consumers would show self-protective behaviors to negative cues such as unsafe food.…”
Section: Loneliness and Consumption Behaviorsmentioning
confidence: 73%
“…Conspicuous consumption refers to the purchase and public display of purchases to communicate the meaning of who one is (Belk, 1988;Griskevicius, Tybur, Sundie, Cialdini, Miller, & Kenrick, 2007;Lee & Shrum, 2012). While conspicuous consumption does not de facto indicate expressions of materialism, conspicuous purchases are naturally alluring for materialists for its signaling function (Shrum et al, 2013(Shrum et al, , 2014.…”
Section: Materialism and Conspicuous Consumptionmentioning
confidence: 99%